GE_GERICHTE P/4730/2024 vom 21. Februar 2024 - GE Cour de justice (2024)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;APPROPRIATION ILLÉGITIME;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL);PRESCRIPTION;PLAINTE PÉNALE;DÉLAI | CPP.310; CP.97; CP.31; CP.137; CP.144